The changes and its significance of peripheral blood NK cells in patients with tuberculous meningitis - Mi, Jie; Liu, Yinping; Xue, Yong; Sun, Wenna; Liang, Yan; Liang, Jianqin; An, Huiru; Wu, Xueqiong (Frontiers in Microbiology, 2024)
Objective: Tuberculous meningitis (TBM) is the most severe form of tuberculosis (TB). The purpose of this study was to explore the relationship between the number of natural killer (NK) cells and adaptive immune status, and disease severity in TBM patients.We conducted a retrospective study on 244 TB patients and 146 healthy control subjects in the 8th Medical Center of the PLA General Hospital from March 2018 and August 2023.The absolute count of NK cells in the peripheral blood of TBM patients was significantly lower than that in normal controls (NC), latent tuberculosis infection (LTBI), and non-severe TB (NSTB) patients (P<0.05). The proportion of TBM patients (48.7%) with a lower absolute count of NK cells than the normal reference value was significantly higher than that in NC (5.2%) and LTBI groups (4.0%) (P<0.05), and slightly higher than that in NSTB group (36.0%) (P>0.05). The absolute counts of lymphocyte subsets in TBM combined with other active TB group, etiology (+) group, IGRA (-) group, and antibody (+) group were lower than that in simple TBM group, etiology (-) group, IGRA (+) group, and antibody (-) group, respectively. The CD3 + T, NK, and B cells in BMRC-stage III TBM patients were significantly lower than those in stage I and stage II patients (P0.05). The counts of CD3 + T, CD4 + T, and B cells in the etiology (+) group were significantly lower than those in the etiology (-) group (P0.05).The absolute counts of lymphocyte subsets in the peripheral blood of TBM patients were significantly decreased, especially in NK cells. The reduction of these immune cells was closely related to the disease severity and had a certain correlation with cellular and humoral immune responses. This study helps to better understand the immune mechanism of TBM and provides reliable indicators for evaluating the immune status of TBM patients in clinical practice.